Global, regional, and national esophageal cancer deaths and DALYs attributable to diet low in vegetables and fruits, 1990–2019: analysis for the global burden of disease study - Cui, Bing; Chen, Aqin; Xu, Chengcheng (Frontiers in Nutrition, 2025)
BackgroundThis study aimed to comprehensively assess the global, regional, and national burden of esophageal cancer (EC) attributable to inadequate vegetable and fruit intake from 1990 to 2019 and explore the potential impact of existing dietary intervention programs on EC prevention.MethodsUsing the Global Burden of Disease Study 2019 (GBD 2019) database, we conducted descriptive analyses stratified by age, sex, Socio-demographic Index (SDI), and regional levels. Temporal trends were assessed using linear regression models, and cluster analysis was employed to explore burden patterns across different GBD regions. Decomposition analysis quantified the contributions of aging, population dynamics, and epidemiological changes to deaths and disability-adjusted life years (DALYs). Frontier analysis was used to evaluate the relationship between dietary risk-related disease burden and sociodemographic progress.ResultsIn 2019, inadequate vegetable and fruit intake contributed to 65,919 global EC deaths, accounting for 0.12% of all deaths, with an age-standardized death rate of 0.81 per 100,000 population. The associated DALYs totaled 16,065,68, representing 0.06% of total global DALYs, with an age-standardized DALY rate of 19.24. The disease burden attributable to insufficient fruit intake (51,210 deaths, 12,497,75 DALYs) was significantly higher than that from inadequate vegetable intake (17,176 deaths, 4,203,09 DALYs). The burden was greater in males than females, peaking in middle-aged groups. Substantial regional differences were observed, with low-SDI regions bearing the highest burden. From 1990 to 2019, while the absolute numbers of deaths and DALYs followed a complex trajectory of initial increase followed by decline, age-standardized rates consistently decreased, reflecting the positive impact of epidemiological improvements. Existing dietary intervention programs, such as subsidies for fruit and vegetable production and health education initiatives, have contributed to a reduction in dietary risk-related disease burden but exhibited varying effectiveness across SDI regions.ConclusionTargeted dietary interventions, such as promoting fruit and vegetable consumption, are critical for the prevention and control of the EC disease burden. Future efforts should focus on optimizing the implementation of current programs, enhancing nutritional supplementation in resource-limited regions, and expanding health education initiatives to achieve broader health benefits.